The calculation and measurement of the natural frequencies of the bucket wheel excavator schrs 1320/4X30 - Gottvald, Jakub (Transport, 2010)
Natural frequencies and shapes are the basic dynamic properties of each structure. On the basis of their knowledge, the sensitivity of the structure to a dynamic load could be estimated. While designing, natural frequencies are based on calculations and numerical simulations. However, computational numerical models do not exactly correspond with real structures and there are many details which have to be simplified. It means that the real natural frequencies of structures may differ from the calculated ones. It is advantageous to verify the calculated results by suitable experimental measurements in case of structures where a dynamic load dominates. The paper deals with the experimental measuring of the natural frequencies of the bucket wheel excavator SchRs 1320/4x30 and a comparison of results obtained from experimental measurements and detailed numerical simulation applying ANSYS. First published online: 10 Feb 2011